Decision Support System Analytical Hierarchy Process in Learning Method Selection. Issue 1 (June 2021) - Azhar, Zulfi; Wakhinuddin,; Waskito,; Effendi, Hansi; Muskhir, Mukhlidi
Abstract: In artificial intelligence lectures at STMIK Royal, lecturers give lectures directly to students. In the implementation of these lectures, there is less variety so that students feel bored and the expected learning objectives are less than optimal. So that a broader knowledge is needed in providing lectures with learning methods to students properly and successfully. In selecting the effective learning method in this study using the Analytical Hierarchy Process (AHP) method, because this method is able to analyze using a number of criteria and selected alternatives. This research method by comparing the matrix with several criteria and alternatives from the results of filling out the questionnaire. This study produces several alternatives in a ranking, namely indirect learning strategies, interactive learning, independent learning and direct learning.